Understanding and assessing governance agents relationships: the contribution of leader-member exchange theory - Osman, Mohammad Noor Hisham; Nahar, Hairul Suhaimi (Elsevier B.V., 2015)
It is a textbook truism that many corporate relationships among governance agents could be theoretically informed by the established agency paradigm. The economic based principal-agent theorization is however falling short of allowing researchers to evaluate the quality of such relationships. In this paper, we depart from the mainstream principal-agent theoretical argumentation by attending to “Leader-Member Exchange” theory (LMX theory), a commonly applied theorization in organizational psychology and communication management literature repertoire. We delineate relevant governance relationships among various governance agents across contexts and subsequently, theoretically argue the applicability of LMX theory in explaining their dyadic relationships. Interfacing LMX theory with corporate governance, we further provide the necessary instruments for measuring governance agents’ relationships quality. Despite the theoretical and argumentative nature of our research endeavour, this paper presents a novel attempt to theoretically demonstrate in light of the subtlety in governance scholarship with respect to the quality of corporate relationships prevailing in any established governance arrangements, that the LMX theory provides an applicable and useful framework through which the dynamics of corporate relationships within the context of corporate governance could be appropriately analyzed and evaluated.